IPhone : the missing manual. - Pogue, David, 1963- (Missing manual., 2018)
The iPhone XS, XS Max, and XR aren't just faster and more powerful than ever--they're also better at all of the things you use an iPhone for. With the latest edition of this bestselling guide, you get a funny, gorgeously illustrated guide to the tips, shortcuts, and workarounds that will turn you into an iPhone master. This easy-to-use book will also get you up to speed on all iOS 12 features, including new Siri shortcuts, Group FaceTime, and improved parental controls. Missing Manual series creator and former New York Times columnist David Pogue helps you accomplish everything from web browsing to watching videos. You'll get up to speed on features such as Dual SIM Support that lets you use two lines on one phone and True Tone technology that adjusts the display to your environment. Pick up this beautiful full-color book and learn how to get the most out of your iPhone.